A cyclic redundancy check‐based non‐coherent receiver for automatic identification system signals. (26th May 2015) - Zhou, H.; Ban, T.; Wang, J.
Summary: A non‐coherent receiver for automatic identification system (AIS) signals is proposed in this paper. The proposed receiver is based on the Viterbi algorithm with cyclic redundancy check (CRC) trellis. It takes bit stuffing into consideration and is designed to simultaneously demodulate decode and correct the received messages. The complexity of the proposed receiver has been reduced with state‐complexity reduction. Simulations prove that the proposed receiver outperforms those AIS receivers without CRC trellis error correction in terms of BER and packet error rate. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We proposed a cyclic redundancy check (CRC)‐based non‐coherent receiver for automatic identification system (AIS) signals received by satellite. With the help of technology for state‐complexity reduction, the complexity of the proposed receiver is reduced. Simulation results proved that the performance of the proposed receiver has been improved compared with those AIS receivers without CRC trellis error correction.